DIGITAL SIGNAL CHAINS IN PARTIAL DISCHARGE MEASUREMENT - Vedral, Josef; Kriz, Martin; Zalis, Karel (International Journal of Computing, 2010)
The paper presents digital techniques in partial discharge measurement. The discharge current pulses are measured on high voltage machines such as power plant generators and transformers. The presented modern digital techniques are suitable for all measurement where impulse energy will be calculated.